EL GÉNERO DICRANOTROPIS FIEBER, 1866, EN LA REPÚBLICA ARGENTINA Y CHILE. (INSECTA: HOMOPTERA: DELPHACIDAE) (Acta Entomológica Chilena, 2022)
This paper deais with the two known representative of the genus Dicranotropis Fieber, 1866, in Argentinaand Chile, D. fuscoterminata (Berg, 1879) and D. acheron Fennah, 1957 respectively.As a result of the study of type specimens from Berg’s collection, in addition to many other collected bythe author in several localities from Argentina, Liburnia fuscoterminata Berg in transferred to Dicranotropisand L. nigricula Berg, 1789 synonymized with this species.Specimens collected by Dr. M. Olmi in the type locality of D. acheron, have permitted the description ofthe female, unknown to date. As D. fuscoterminata and D. acheron are morphologically very similar, bothspecies are comparatively analized and illustrated.